2017
DOI: 10.1108/prt-08-2015-0077
|View full text |Cite
|
Sign up to set email alerts
|

Response surface methodology (RSM) mediated interaction of media concentration and process parameters for the pigment production by Monascus purpureus MTCC 369 under solid state fermentation

Abstract: Purpose This paper aims to extract colour from micro-organisms (as a source of natural pigments) using agro-industrial substrates to replace synthetic media by solid state fermentation. Nature is filled with colours. Due to health and environmental consciousness among people, use of synthetic colour has declined, and so the need to develop colour from cheap and easily available natural sources (plants, animals, micro-organisms and algae) using a cost-effective technique with higher yield and rapid growth. Mona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Preliminary tests identified that water content <12 per cent in the CB decreased fermentation or prevented production of the pigments, and because of this, the ratio 1:1 of water (mL): substrate (g) was used in SSF. The time (4, 8, 12 and 16 days) (Dikshit and Tallapragada, 2011), temperature (16, 24 and 32°C) (Dikshit and Tallapragada, 2011; Jamaluddin et al , 2016; Sehrawat et al , 2017), and amount of spores (10 5 , 10 6 and 10 7 spores for mL) (Srianta et al , 2016; Bei et al , 2018) used in this fermentative process were chosen based on reports from the literature in other subtracts. One SSF treatment was considered for new ingredient with red color production.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary tests identified that water content <12 per cent in the CB decreased fermentation or prevented production of the pigments, and because of this, the ratio 1:1 of water (mL): substrate (g) was used in SSF. The time (4, 8, 12 and 16 days) (Dikshit and Tallapragada, 2011), temperature (16, 24 and 32°C) (Dikshit and Tallapragada, 2011; Jamaluddin et al , 2016; Sehrawat et al , 2017), and amount of spores (10 5 , 10 6 and 10 7 spores for mL) (Srianta et al , 2016; Bei et al , 2018) used in this fermentative process were chosen based on reports from the literature in other subtracts. One SSF treatment was considered for new ingredient with red color production.…”
Section: Methodsmentioning
confidence: 99%
“…As synthetic colorant affects human health (Sehrawat et al , 2016, 2017a, 2017b). So, the modern world needs to look for food colorants of natural origin, which exhibit high antioxidant activity and impart color when added to food.…”
Section: Introductionmentioning
confidence: 99%
“…Response surface and artificial neural network methodologies are commonly applied tools for modeling, optimization and statistical evaluations in biotechnological practices (Kalil et al, 2000). Production, modeling and optimization applications for enzymes, bio-surfactants, ethanol, gelling agents, pharmaceutical compounds, bio-fuels, pigments, and fermentation medium have been studied recently (Basri et al, 2007;Desai et al, 2008;Kashkouli et al, 2011;Nelofer et al, 2012;Zou et al, 2013;Pilkington et al, 2014;Dikshit and Tallapragada, 2015;Maran and Priya, 2015;del Rio-Chanona et al, 2016;Sehrawat et al, 2017;Wei et al, 2017;Shafi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%